2000
DOI: 10.1182/blood.v96.5.1723.h8001723_1723_1732
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, a new member of the family of soluble defense collagens, negatively regulates the growth of myelomonocytic progenitors and the functions of macrophages

Abstract: We investigated the functions of adiponectin, an adipocyte-specific secretory protein and a new member of the family of soluble defense collagens, in hematopoiesis and immune responses. Adiponectin suppressed colony formation from colony-forming units (CFU)—granulocyte-macrophage, CFU-macrophage, and CFU-granulocyte, whereas it had no effect on that of burst-forming units—erythroid or mixed erythroid-myeloid CFU. In addition, adiponectin inhibited proliferation of 4 of 9 myeloid cell lines but did not suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0
20

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 52 publications
3
116
0
20
Order By: Relevance
“…Previous studies have proven that fat mass, especially visceral fat mass, is associated with inflammatory markers and metabolic parameters. [29][30][31] Consistent with those studies, our study showed that body fat was related to the MetS and its components, independent of muscle mass and other potential confounders. However, our findings did not support that LMM is an independent risk factor for MetS.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have proven that fat mass, especially visceral fat mass, is associated with inflammatory markers and metabolic parameters. [29][30][31] Consistent with those studies, our study showed that body fat was related to the MetS and its components, independent of muscle mass and other potential confounders. However, our findings did not support that LMM is an independent risk factor for MetS.…”
Section: Discussionsupporting
confidence: 91%
“…Neither the insulin sensitizing effect of adiponectin nor its anti-inflammatory effect in both humans and rodents is disputable. The mechanistic underpinning of adiponectin function includes: 1) Promoting the M2 anti-inflammatory polarization of macrophages and their phagocytic activity against apoptotic cells [78,79]; 2) Modulating T cells activation by inducing adiponectin receptors expression on the surface of T cells after antigen stimulation, followed by apoptosis-mediated suppression of antigen specific T cells expansion [80]; 3) Modulating the inflammatory function of natural killer (NK) cells by suppressing their Toll Like Receptor (TLR)-mediated interferon gamma (IFNγ) production without affecting their cytotoxicity [80]; 4) Suppressing transcription of TNFα, IL6 and other pro-inflammatory factors by inhibiting the IKKβ/NF-κB signaling inflammatory pathways [81][82][83][84]; 5) Increasing PPARγ2 expression in adipocytes [82]; and 6) Inducing IL10 expression [85,86].…”
Section: Recruitment Of Macrophages and Other Inflammatory Cells To Amentioning
confidence: 99%
“…Adiponectin acts as an antiatherogenic hormone through the inhibition of vascular smooth muscle cell proliferation, as well as macrophage functions. (20,21) Adiponectin also has an antidiabetic action through the modulation of glucose and fatty acid metabolism and insulin sensitivity. (22)(23)(24) In fact, the circulating level of adiponectin has been reported to be inversely related to body mass index (BMI) (25)(26)(27) and to be reduced in conditions of insulin resistance such as visceral obesity and type 2 diabetes.…”
mentioning
confidence: 99%